Manajemen anestesi pada fraktur multiple os femur dan os tibia: Sebuah laporan kasus - Ayu Dinda Fatimah (SEHATI: Jurnal Kesehatan, 2022)
Fracture is a break in the continuity of bone, joint bone, epiphyseal cartilage, which is total or partial. Currently musculoskeletal disease has become a problem that is often found in health care centers around the world. Overall incidence of fractures was 11.3 in 1,000 per year, in males was 11.67 in 1000 per year, whereas in 10.65 in 1,000 women per year. The classic symptom is a history of trauma fracture, pain and swelling in the broken bones, deformity, musculoskeletal dysfunction, breaking the continuity of the bone, and neurovascular disorders. Principles of fracture treatment is to restore the position of the fracture to its original position (reposition) and held that position during the healing of fractures (immobilization). Special in open fractures, must be considered the danger of infection, either general or local infection. Mr. A 30 years old came with complaints of difficulty moving his left leg after a traffic accident 3 months ago and was taken to a sangkal putung but it didn't heal so he was taken to the hospital and got multiple fractures of the tibia and femur. The patient underwent surgery with the ORIF procedure under general anesthesia. Preoperative, intraoperative, and postoperative management needs to be done correctly and completely to support the success of the operation.